Role of Coagulation Irregularities in Cholangiocarcinoma: A review - Hamid, Hafsa; Coric, Sladjana; Rafaqat, Saira; Gluscevic, Sanja; Mercantepe, Filiz; Klisic, Aleksandra (Journal of Medical Biochemistry, 2025)
Cholangiocarcinoma (CCA) is a malignancy that originates from the biliary epithelium, presenting either intrahepatically or extrahepatically. It is characterized by a late-stage diagnosis and a poor overall prognosis. D-dimer, a biomarker indicative of coagulation and fibrinolysis activation, is believed to play a significant role in cancer progression, with elevated plasma levels correlating positively with metastatic disease and advanced cancer stages. In intrahepatic CCA, fibrinogen has been identified as an independent prognostic factor, associated with adverse outcomes and reflects systemic inflammatory responses. The increased expression of urokinase-type plasminogen activator has been linked to lymphatic invasion and metastatic spread in CCA patients. Additionally, a preoperative elevation in prothrombin time may predict reduced survival rates for individuals underging potentially curative surgical interventions. P-selectin, which interacts predominantly with leukocyte ligands, has the potential to promote tumorigenesis and facilitate metastatic dissemination of mucin-producing carcinomas. Moreover, prolonged activated partial thromboplastin time may provide valuable insights into the extent of parenchymal involvement in CCA. This review aims to elucidate the role of coagulation abnormalities within the pathophysiology of cholangiocarcinoma.